HOW THE COMMITMENT TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS IMPACTS POOR WOMEN IN ACEH PROVINCE, INDONESIA - Fitri, Cut Dian; Vonda, Pocut Ismyati (Universitas Islam Negeri Ar-Raniry, 2016)
This paper aims to examine how the commitment to achieve Sustainable Development Goals impacts poor women in Aceh Province, Indonesia. It starts with a brief introduction on the poverty condition in Aceh Province and Indonesia as well as Sustainable Development Goals (SDGs). Then, go on tolook at the nature of SDGs as a new global agenda to see what challenge it has in the implementation and what is offered by SDGs in relation to poor women issue. This followed by an assessment on what have been done by the national government (Republic of Indonesia) and local government (Aceh Province) in response to this agenda. Finally, a conclusion and some recommendations will be drawn as a closing part of this paper